MOISTURE EFFECTS ON THE BUILDINGS ENCLOSING STRUCTURES - Semko, O. V.; Mahas, N. M.; Mishchenko, A. R.; Mishchenko, R. R. (Academic journal Industrial Machine Building Civil Engineering, 2018)
Analysis of the most common damages due to moisture effects on brick, reinforced-concrete and wooden buildings enclosing structures has been carried out. Causes of their occurrence and prevention ways have been analyzed. The most dangerous moisture types such as constructional, soil, atmospheric, operational, hygroscopic and condensed have been outlined. Measures to ensure protection against water-saturation of building elements such as eaves size, walls waterproofing, available airways, protective painting, hydrophobic impregnation, sufficient ventilation, heating, water supply systems and draining timely repairs have been recommended.